Evaluation of the Histology of Gonads in Ramirezi (Mikrogeophagus ramirezi) as a Response to Variations in Feeding Ratio - Azizah Azizah; Munti Sarida; Yudha Trinoegraha Adiputra; Yeni Elisdiana (Jurnal Veteriner, 2025)
Nutritional management is a crucial factor in optimizing the reproductive performance of fish. This study was aimed to evaluate the histological characteristics of the gonads of ramirezi (Mikrogeophagus ramirezi) in response to variations in feed ratios. The feeding trial was conducted over a period of 45 days with four different treatments. The experimental design involved the administration of artificial feed and Tubifex worms in varying ratios: (A) 3:0, (B) 0:3, (C) 2:1, and (D) 1:2. Gonads (testes and ovaries) were collected at the beginning and end of the treatment.  Histological analysis using hematoxylin-eosin staining, to assess the developmental stages based on tissue structure and germ cell stages. Observations revealed significant differences in gonadal maturity levels among the treatments. In the testes, treatment A exhibited a predominance of spermatogonia, while the treatment with a 1:2 ratio (treatment D) displayed seminiferous tubule lumens filled with spermatozoa. The ovaries showed development from Primary Growth Oocyte (PG) to the vitellogenic stage, particularly in treatment D. The combination of artificial feed and Tubifex worms at a 1:2 ratio (treatment D) significantly accelerated gonadal maturation in both male and female M. ramirezi. These findings underscore the importance of integrating high-quality natural feed in the management of broodstock and reproduction within small-scale aquaculture systems.